2014
DOI: 10.1155/2014/754182
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking with Hypoosmolar Riboflavin Solution in Keratoconic Corneas

Abstract: Purpose. To report the 12-month outcomes of corneal collagen cross-linking (CXL) with a hypoosmolar riboflavin and ultraviolet-A (UVA) irradiation in thin corneas. Methods. Eight eyes underwent CXL using a hypoosmolar riboflavin solution after epithelial removal. The corrected distance visual acuity (CDVA), manifest refraction, the mean thinnest corneal thickness (MTCT), and the endothelial cell density (ECD) were evaluated before and 6 and 12 months after CXL. Results. The MTCT was 413.9 ± 12.4 μm before trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
(44 reference statements)
0
15
0
1
Order By: Relevance
“…16 Such inconsistencies may introduce variability in CXL stiffening and limit its efficacy. 17,26,27 The current study demonstrates this variability with corneal swelling thickness ranging from 401 to 519 μm after swelling. Despite this unpredictability, the current study shows good CXL success.…”
Section: Discussionmentioning
confidence: 54%
“…16 Such inconsistencies may introduce variability in CXL stiffening and limit its efficacy. 17,26,27 The current study demonstrates this variability with corneal swelling thickness ranging from 401 to 519 μm after swelling. Despite this unpredictability, the current study shows good CXL success.…”
Section: Discussionmentioning
confidence: 54%
“…But Hafezi et al study did not include endothelial cell count measurements which could verify the safety of the technique. Gu et al [ 24 ] investigated the safety and efficacy of using hypoosmolar riboflavin solution (0.1%) and UVA cross-linking for the treatment of keratoconus with the thin cornea (mean thinnest CT was 413.9 ± 12.4 μ m and 381.1 ± 7.3 μ m with and without epithelium). During a 12-month follow-up, the mean keratometric ( K ) value improved from 58.7 ± 3.5 diopters (D) to 57.7 ± 4.9 D ( P = 0.611), and the endothelial cell density (ECD) was 2731.4 ± 191.8 cells/mm 2 before treatment and decreased to 2722.5 ± 211.5 cells/mm 2 ( P = 0.208) at 6 months after treatment and returned to 2733.4 ± 222.6 cells/mm 2 ( P = 0.327) at 12 months.…”
Section: Procedures and Modificationmentioning
confidence: 99%
“…Hafezi et al, as first in 2009, proposed this technique for corneas thinner than 400 microns, and they observed a stabilization of corneal ectasia in 20 eyes treated with this technique, and similar results were later confirmed by other authors [29][30][31]. However, after this technique was reported permanent corneal scars and permanent stromal scar, and Gu et al showed a decreased endothelial cell density 3 months after the treatment [32,33]. Some authors believe that this technique is not reliable and that is important monitoring the corneal thickness throughout CXL treatment with hypo-osmolar riboflavin because artificial cornea swelling effect is transient.…”
Section: Discussionmentioning
confidence: 78%